A Tribute to Jack Welch: Manager of the Century - Mohd Ossama (International Journal of Engineering and Management Research, 2020)
Jack Welch was the CEO of General Electric (GE) from 1981 – 2001, when the company expanded significantly, its worth grew multifold, he was named -Manager of the Century by the Fortune magazine. The company saw increased market value from around 14 billion to 410 billion odd under his stewardship. This essay tries to highlight the importance of his leadership skills and his business decisions that shaped the course for the company. He has been an icon for future managers, he died in 2020.